An Investigation of a Novel Dural Repair Device for Intraoperative Incidental Durotomy Repair - Shenoy, Kartik; Donnally, Chester J.; Sheha, Evan D.; Khanna, Krishn; Prasad, Srinivas K. (Frontiers in Surgery, 2021)
Incidental durotomies, or dural tears, can be very difficult and time consuming to repair properly when they are encountered in confined spaces. A novel dural repair device was developed to address these situations. In this paper, the novel device was assessed against the use of traditional tools and techniques for dural repairs in two independent studies using an intricate clinical simulation model. The aim was to examine the results of the two assessments and link the outcomes to the clinical use of the novel device in the operating room. The novel device outperformed conventional techniques as measured by dural repair time, CSF leak pressure and nerve root avoidance in the simulation. The results were generally replicable clinically, however, numerous additional clinical scenarios were also encountered that the simulation model was unable to capture due to various inherent limitations. The simulation model design, potential contributors to watertightness, clinical experiences, and limitation are discussed